Concentrated Violence: The Influence of Criminal Activity and Governance on Prison Violence in Latin America - Peirce, Jennifer (International criminal justice review, 2020)
In this article, we explore patterns of prison violence in five Latin American countries: Argentina, Brazil, Chile, El Salvador, and Peru. Drawing on data from prisoner surveys conducted in 49 facilities with over 4,400 prisoners, we analyze the association between facility-level and individual-level rates of experiences of violence and the extent of perceived criminal activity committed in or ordered from inside prisons. Contrary to classical theory, neither poor prison conditions nor prior delinquent experience is directly associated with increased violence. Rather, we demonstrate that prison facilities with more widespread criminal activity inside have higher rates of prison violence. Further, within a given facility, prisoners with closer ties to criminal activity have more pre-incarceration criminal exposure and are also more likely to experience violence inside prison; this reflects research on victim-offender overlap. At a general level, our study shows that involvement in the sub-rosa economy of the prison increases one’s risk of violence in prison. We consider how common features of Latin American prisons—scarce state-provided resources, permeability to people on the outside, and more prisoner-led governance—explain these dynamics of violence inside prisons. Where prisoner-led governance is more consolidated—such as in Brazil and El Salvador—violence appears to be less common, even if criminal activity is prevalent, compared to countries where prison governance is combined or contested between authorities and prisoners. These findings suggest that prison violence reduction policies should respond to the real needs and strategies of incarcerated people rather than simply impose more control.